Leveraging Research and Demanding Proof In Response To Legislative Attacks on DEI in U.S. Higher Education - Shaun Harper (AERA Open, 2025)
More than 50 years of research confirms the value that diversity, equity, and inclusion (DEI) policies, programs, and professional roles add to college and university campuses. Despite this, governors, state legislators, federal policymakers, and a U.S. President have signed executive orders, issued “Dear Colleague” letters, and enacted policies in recent years that have defunded or eliminated DEI initiatives. Many DEI professionals have lost their jobs; grants to scholars studying DEI-related topics have been paused and canceled. This article is a call for greater reliance on and appreciation for empirical evidence about the educational benefits of DEI in higher education. It also places the burden of proof on DEI opponents who make enormously consequential, unsubstantiated claims. Lastly, five common myths and exaggerations about DEI are juxtaposed with evidence from various trustworthy sources.